Epigenetic Underpinnings of Inflammation: A Key to Unlock the Tumor Microenvironment in Glioblastoma - Chen, Nian; Peng, Cheng; Li, Dan (Frontiers in Immunology, 2022)
Glioblastoma (GBM) is the most common malignant brain tumor in adults, and immunotherapies and genetic therapies for GBM have evolved dramatically over past decade, but GBM therapy is still facing dilemma due to the high recurrence rate. Inflammatory microenvironment is a general signature of tumor that accelerates epigenetic changes in GBM and helps tumor avoiding immunological surveillance. GBM tumor cells and glioma-associated microglia/macrophages are the primary contributors to the inflammatory condition, meanwhile the modification of epigenetic events including DNA methylation, non-coding RNAs, and histone methylation and deacetylases involve in this pathological process of GBM, finally result in exacerbating proliferation, invasion and migration of GBM. While, the histone deacetylase inhibitors, DNA methyltransferases inhibitors and RNA interference could reverse the inflammatory landscapes and inhibit GBM growth and invasion. Here, we systematically review the inflammatory associated epigenetic changes and regulations in microenvironment of GBM, aiming to provide a comprehensive epigenetic underlying recognizing of inflammation in GBM.